Determinación de la prevalencia y factores de riesgo de demencia senil en Adultos Mayores del Centro del Día del Cantón Gonzanamá. - Luna Salinas, Edgar Miguel (2016)
According to the high prevalence of dementia related to old age affecting people worldwide; is the importance of knowing the incidence in our population. The present research on the topic: "DETERMINATION OF THE PREVALENCE AND RISK FACTORS DEMENTIA IN ELDERLY CENTER DAY CANTON GONZANAMÁ" it held in the Day Center Canton Gonzanamá come very often where a lot of elderly patients, in order to determine the prevalence and risk factors for dementia. Since psychiatric diagnoses are not studied in depth, thus associated data between dementia and other demographic variables. The study method is quantitative, descriptive cross-sectional. Whose number is 150 patients older adults, who after making the respective diagnostic analysis, it was determined the presence of 5 (3.33%) cases of dementia specifically Alzheimer's disease, with greater predominance of women with 60% compared to 40% in men, most prevalent in patients who worked as teachers and to a lesser hereditary percentage, recommending awareness and improve attitudes of health personnel to screen all patients holistically thinking of all aspects, not only in the physical and biological branch if not in the psychological and environmental branch of the patient. Key words: Risk factors, senile dementia, elderly.